Monitoring During Hepatic Radiofrequency Ablation (RFA): Comparison of Real-Time Ultrasound Elastography (RTE) and Contrast-Enhanced Ultrasound (CEUS): First Clinical Results of 25 Patients - Wiggermann, P.; Brünn, K.; Rennert, J.; Loss, M.; Wobser, H.; Schreyer, A. G.; Stroszczynski, C.; Jung, E. M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To evaluate the reliability of ultrasound elastography for delineating thermal ablation defects post-radiofrequency ablation (RFA) by comparing lesion dimensions determined by real-time elastography (RTE) with the findings of contrast-enhanced ultrasound (CEUS).Materials and Methods: A total of 21 malignant liver tumors were percutaneously ablated using RFA. Color-coded elastography and CEUS were performed by one experienced examiner, using a 1 – 5 MHz multi-frequency convex transducer (LOGIQ E9, GE). Lesions were examined using CEUS and real-time elastography (RTE) to assess ablation defects. Measurements of lesions (long axis, short axis, and area) representing the same image plane used for elastography were taken during CEUS examination and compared to the measurements obtained from the elastograms. All measurements were performed by two independent observers.Results: A statistically significant correlation in vivo between RTE and CEUS measurements with respect to the lesion’s principal axis and area (r = 0.876 long axis, r = 0.842 short axis and r = 0.889 area) was found. Inter-rater reliability assessed with the concordance correlation coefficient was substantial for all measurements (ρc ≥ 0.96) Overall, elastography slightly underestimated the lesion size, as judged by the CEUS images.Conclusion: These results support that RTE could potentially be used for the routine assessment of thermal ablation therapies.
Keywords: abdomen; liver; ablation procedures; interventional procedures